Penyusunan Kamus Hukum Ekonomi Syariah sebagai Upaya Pengembangan Institusi - Rohman, Moh. Faizur; Arifin, Moch. Zainul; Samun, Samun (Maliyah : Jurnal Hukum Bisnis Islam, 2023)
The research with the title Efforts to Develop the HES Study Program through the Compilation of a Sharia Economic Law Dictionary (HES Dictionary) is a literature study that aims to find out the steps for compiling the HES Dictionary and find out the results of the preparation of the Sharia Economic Law Dictionary. This research is included in the type of qualitative descriptive research that describes the steps of compiling a dictionary and describes the terms in Islamic Economic Law, identified through the study of documents derived from data sources. The results obtained related to the steps of compiling a dictionary are through the stages of designing a dictionary, identifying reference materials, determining reference materials, determining the format, finishing and evaluation. From the evaluation results, it was found that the compiled dictionary design was very helpful in supporting the learning process, especially in the HES Book Review course and the Arabic for HES course. This was based on the results of the evaluation of the discussion participants because so far, they had only relied on pure Indonesian Arabic dictionaries without knowing the whole meaning of the vocabulary. The discussion participants also stated that this HES dictionary could help dictionary users overcome difficulties in understanding various Arabic terms related to mu'amalah fiqh, especially in taking text studies and Arabic for HES courses.